2018
DOI: 10.3390/genes9120588
|View full text |Cite
|
Sign up to set email alerts
|

Systems Analysis of Transcriptomic and Proteomic Profiles Identifies Novel Regulation of Fibrotic Programs by miRNAs in Pulmonary Fibrosis Fibroblasts

Abstract: Fibroblasts/myofibroblasts are the key effector cells responsible for excessive extracellular matrix (ECM) deposition and fibrosis progression in both idiopathic pulmonary fibrosis (IPF) and systemic sclerosis (SSc) patient lungs, thus it is critical to understand the transcriptomic and proteomic programs underlying their fibrogenic activity. We conducted the first integrative analysis of the fibrotic programming in these cells at the levels of gene and microRNA (miRNA) expression, as well as deposited ECM pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 41 publications
3
25
0
Order By: Relevance
“…In several cases, our methodology confirmed associations that had previously been noted. We found Wnt signaling, TGF-β signaling, and ECM associated genes to be upregulated ( Table 1 ), which has been confirmed at the mRNA and miRNA level in SSc fibroblasts [ 40 ]. The Wnt/β -catenin signaling pathway is over activated in SSc patients and expression of WIF1 , a Wnt pathway antagonist, is decreased in SSc patients [ 41 ], likely through a reactive oxygen species-dependent transcriptional repression mechanism [ 42 ].…”
Section: Discussionsupporting
confidence: 64%
“…In several cases, our methodology confirmed associations that had previously been noted. We found Wnt signaling, TGF-β signaling, and ECM associated genes to be upregulated ( Table 1 ), which has been confirmed at the mRNA and miRNA level in SSc fibroblasts [ 40 ]. The Wnt/β -catenin signaling pathway is over activated in SSc patients and expression of WIF1 , a Wnt pathway antagonist, is decreased in SSc patients [ 41 ], likely through a reactive oxygen species-dependent transcriptional repression mechanism [ 42 ].…”
Section: Discussionsupporting
confidence: 64%
“…Previous studies have revealed that ECM protein expression plays an important role in the fibrotic process in IPF lungs (Vicens-Zygmunt et al, 2015). Excessive accumulation of ECM in the alveolar parenchyma and progressive scarring of lung tissue are major characteristics of IPF (Knudsen et al, 2017), and some studies have used this protein expression level as a criterion for evaluating treatment outcomes (Molina-Molina et al, 2018;Mullenbrock et al, 2018). Altogether, migration is strongly influenced by topology and composition of the ECM including integrin ligands, and the hub gens and hub miRNAs might play an important role in IPF progression with the change of ECM.…”
Section: Disscusionmentioning
confidence: 99%
“…Many of those genes were previously found to be fibrogenic, including those encoding NOX4, CTGF, PERIOSTIN, LOX, and CDH2. [15][16][17] Induction of NOX4, which encodes NADPH oxidase 4, is associated with the production of reactive oxygen species (ROS) and with several important signaling events, including LPS signaling and inflammasome activation. 18 These findings suggested that NOX4 plays an important role in the pathogenesis of myofibroblasts.…”
Section: Resultsmentioning
confidence: 99%